2020
DOI: 10.1111/jpn.13447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two zinc supplementation levels and two zinc and copper sources with different solubility characteristics on the growth performance, carcass characteristics and digestibility of growing‐finishing pigs

Abstract: The present study was conducted to evaluate the effect of two Zn supplemented levels and two Zn and Cu sources (sulphate and hydroxychloride) on growing‐finishing pigs. An in vitro study and an in vivo study were conducted. In the in vitro study, Zn solubility from each source at different Zn supplementation levels was evaluated, as well as the phytic phosphorus (PP) solubility derived from the interaction or not with phytic acid at similar conditions to those found in digestive tract. The most critical intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
5
1
2
Order By: Relevance
“…Most studies suggest that Cu enhances performance during early growing and finishing periods with less or no response during the late finishing period ( Hastad et al, 2001 ). However, in our study and other research, the results were observed at the end of the finishing period, demonstrating that the CHC can be more effective in pig heavier at the market weight ( Coble et al, 2017 ; Villagómez-Estrada et al 2021 ).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Most studies suggest that Cu enhances performance during early growing and finishing periods with less or no response during the late finishing period ( Hastad et al, 2001 ). However, in our study and other research, the results were observed at the end of the finishing period, demonstrating that the CHC can be more effective in pig heavier at the market weight ( Coble et al, 2017 ; Villagómez-Estrada et al 2021 ).…”
Section: Discussioncontrasting
confidence: 59%
“…The results of the present study are partially consistent with findings of Van Kuijk et al (2019) that reported based on a meta-analysis that pigs fed 80 mg Zn/kg as hydroxychloride associated with 15 mg Cu/kg have an improvement in lean meat percentage and also at the end of the finisher period, the gain:feed ratio and ADG were both raised by 3.9% compared with those fed sulfates. Villagómez-Estrada et al (2021) also observed that pigs fed hydroxychloride source showed an improvement by 0.75% carcass yield and tended an increase by 5.94% the ADG at the end of the finisher period than those fed sulfates, regardless of Zn level (20 or 80 mg Zn/kg) associated with 15 mg Cu/kg as CuSO 4 in all treatments.…”
Section: Discussionmentioning
confidence: 59%
“…Another important characteristic of HTM is related to their crystalline structure [ 25 ]. This structure results in a low solubility above pH 4 [ 9 ], possibly leading to a more gradual release throughout the gastrointestinal tract. As a result, more minerals are available later in the intestine of HTM-fed birds.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloride trace minerals (HTM) are a good example of a more bioavailable mineral source in broilers compared to sulphate trace minerals (STM) [ 7 ]. In addition, HTM do have a unique crystalline structure that is not readily soluble at a pH above 4 [ 8 , 9 ]. Moreover, HTM are much less reactive in the feed than STM, and do not interact with antinutritional factors such as phytate [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Головною умовою, яка забезпечує інтенсивність обміну речовин, є достатнє і збалансоване потрапляння в організм будівельного матеріалу, що включає як органічні так і неорганічні речовини (Villagómez-Estrada et al, 2020).…”
Section: вступunclassified